2021
DOI: 10.3906/sag-2011-169
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hospital-acquired acute kidney injury on Covid-19 outcomes in patients with and without chronic kidney disease: a multicenter retrospective cohort study

Abstract: Background/aim Hospital-acquired acute kidney injury (HA-AKI) may commonly develop in Covid-19 patients and is expected to have higher mortality. There is little comparative data investigating the effect of HA-AKI on mortality of chronic kidney disease (CKD) patients and a control group of general population suffering from Covid-19. Materials and methods HA-AKI development was assessed in a group of stage 3–5 CKD patients and control group without CKD among adult patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
4
8
0
1
Order By: Relevance
“…In the group of patients with eGFR ≥ 60 mL/min/1.73 m 2 , the rates were 23.25% and 9.64% ( p < 0.001), respectively. Our results are consistent with observations made by other authors [ 18 , 34 , 35 , 36 ]. In a UK population-based cohort study, increased risk of death was evident from eGFR 45–59 mL/min/1.73 m 2 in people with type 1 and type 2 diabetes [ 37 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the group of patients with eGFR ≥ 60 mL/min/1.73 m 2 , the rates were 23.25% and 9.64% ( p < 0.001), respectively. Our results are consistent with observations made by other authors [ 18 , 34 , 35 , 36 ]. In a UK population-based cohort study, increased risk of death was evident from eGFR 45–59 mL/min/1.73 m 2 in people with type 1 and type 2 diabetes [ 37 ].…”
Section: Discussionsupporting
confidence: 94%
“…It is believed that there is a correlation between renal function impairment and increased risk of death in patients with COVID-19 [ 20 , 33 , 34 , 35 ]. In this study of nearly 2000 adults with COVID-19, we found that the mortality rate during hospitalization was much higher in patients with eGFR < 60 mL/min/1.73 m 2 than in patients with eGFR ≥ 60 mL/min/1.73 m 2 at admission (29.38% vs. 10.36%, respectively; p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“… 1 Preexistent chronic renal disease was identified as a risk factor for acute kidney injury during the hospital stay. 34 , 35 , 36 , 37 We have also demonstrated that impaired renal allograft function presents a risk factor for developing post‐COVID‐19 complications in general. All except one patient with acute allograft dysfunction and/or development of proteinuria already had chronic allograft dysfunction.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, RSV values for the terms “amyloidosis” and “acute kidney injury” were increased compared to the previous 4 years in both time intervals. We cannot explain this increase for the term “amyloidosis.” However, various studies have reported that the incidence of AKI in patients with COVID-19 is between 3 and 15% and this is associated with increased mortality (Zhou et al 2020 ; Sİpahİ et al 2020 ; Adapa et al 2020 ; Öztürk et al 2021 ). Also, AKI rates are 14.5–50% in patients with severe COVID-19 infection in the intensive care unit (Zhou et al 2020 ; Sİpahİ et al 2020 ; Adapa et al 2020 ; Öztürk et al 2021 ; Dirim et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, various studies have reported that the incidence of AKI in patients with COVID-19 is between 3 and 15% and this is associated with increased mortality (Zhou et al 2020;Sİpahİ et al 2020;Adapa et al 2020;Öztürk et al 2021). Also, AKI rates are 14.5-50% in patients with severe COVID-19 infection in the intensive care unit (Zhou et al 2020;Sİpahİ et al 2020;Adapa et al 2020;Öztürk et al 2021;Dirim et al 2021). As this condition is known to be associated with COVID-19 since the early stage of the pandemic, the initial increase in RSV for search query "acute kidney injury" is not unexpected.…”
Section: Discussionmentioning
confidence: 99%